2021
DOI: 10.1007/s00500-021-06061-0
|View full text |Cite|
|
Sign up to set email alerts
|

G-optimal designs for hierarchical linear models: an equivalence theorem and a nature-inspired meta-heuristic algorithm

Abstract: Hierarchical linear models are widely used in many research disciplines and estimation issues for such models are generally well addressed. Design issues are relatively much less discussed for hierarchical linear models but there is an increasing interest as these models grow in popularity. This paper discusses the G-optimality for predicting individual parameters in such models and establishes an equivalence theorem for confirming the G-optimality of an approximate design. Because the criterion is non-differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Most recently, a variant of CSO called CSO with mutated agent (CSO-MA) was also used to find G-optimal designs for various hierarchical models with random effects (X. Liu et al, 2021;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, a variant of CSO called CSO with mutated agent (CSO-MA) was also used to find G-optimal designs for various hierarchical models with random effects (X. Liu et al, 2021;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, quantum PSO, DE, ICA and a modified CSO algorithm have been recently used to newly find various types of optimal designs for generalized linear models, like the logistic and the negative binomial regression models with several interacting factors, with and without random effects (Lukemire et al, 2019; Masoudi et al, 2019; Stokes et al, 2020; Xu et al, 2019). Most recently, a variant of CSO called CSO with mutated agent (CSO‐MA) was also used to find G ‐optimal designs for various hierarchical models with random effects (X. Liu et al, 2021; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others include Chen et al (2015) and Masoudi et al (2017), who found standardized maximin optimal designs under a nondifferentiable criterion for a few enzyme kinetic models that required solving multiple nested optimization problems over different spaces. In addition, Masoudi et al (2019) applied ICA and found Bayesian optimal designs and, both Zhang et al (2020) and Liu et al (2021) modified the CSO algorithm and found optimal designs for different types of regression models with random effects. A most recent application using PSO and Genetic Algorithm is described in Ushijima et al (2021), where they found efficient designs for groundwater models after the complex models were simplified using a Galerkin method and a Proper Orthogonal Decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…There are few tuning parameters required of the algorithm and the knowledge of good solutions is retained by all particles, and particles in the swarm share information between, which makes the algorithm easily escape from local minima and converge at a fast rate. Recently, different versions of PSO have been used to solve all kinds of optimal design problems (see Chen et al [34], Zhou et al [35], and Liu et al [36]). In the following we give a summary of the PSO algorithm for completeness.…”
Section: Particle Swarm Optimization Algorithmmentioning
confidence: 99%